Archie. Volume six - Waid, Mark, 1962-; Flynn, Ian, 1982- (Archie Comic Publications, 2018)
It all comes down to this! The Riverdale gang--held hostage by Cheryl Blossom's father! Reggie--at last paying for his crimes! And when all is said and done, Riverdale is turned upside down once more--Amazon.